Isolation of pregnancy-associated glycoproteins (PAG) from water buffalo (Bubalus bubalis) placenta by use of Vicia villosa bound agarose affinity chromatography - J.F. Beckers (Italian Journal of Animal Science, 2010)
The present study describes the isolation and characterisation of new PAG molecules extracted from mid- and late-pregnancy placentas in the water buffalo (Bubalis bubalis). After extraction, acid and ammonium sulphate precipitation and DEAE chromatography water buffalo PAG (wbPAG) were enriched by Vicia villosa agarose (VVA) affininity chromatography. As determined by Western blotting with anti-PAG-sera, apparent molecular masses of immunoreactive bands from VVA peaks ranged from 59.5 to 75.8 kDa and from 57.8 to 80.9 kDa in the mid- and late- pregnancy placenta respectively. Aminoterminal microsequencing of proteins allowed the identification of three distinct wbPAG sequences wich have ben deposed in the SwissProt database: RGSXLTIHPLRNIRDFFYUG (Acc. n. P85048), RGSXLTILPLRNIID (P85049) and RGSXLTHLPLRNI (P85050). Their comparison to those previously identified revealed that two of them were new since they have not been described yet. Our results confirm the suitability of VVA chromatography in enrichment of multiple PAG molecules expressed in buffalo placenta. Productions of specific antisera can be very useful in immonoistochemical and immunocyitochemical studies of PAG expression in fetomaternal interfaces. Purified native PAG are also required for development on specific immoassays (RIA/ELISA) currently used for pregnancy diagnosis and physiological investigation in farm animal.